2011
DOI: 10.1002/ps.2185
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to Bacillus thuringiensis Cry1Ac toxin in Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) from India

Abstract: Based on dominance, degree of dominance and backcross values, resistance was inferred to be polygenic, autosomal and inherited as a recessive trait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…Kaur and Dilawari (2011), under laboratory conditions, showed that the resistance of Helicoverpa armigera to Cry1Ac was autosomal, partially recessive and polygenic. Similar conclusions were obtained for populations of Plutella xylostella (Sayyed et al, 2000), Heliothis virescens , and Pectinophora gossypiella (Kaur and Dilawari, 2011).…”
Section: Sustainability Of Biocontrol Agent Efficacymentioning
confidence: 99%
“…Kaur and Dilawari (2011), under laboratory conditions, showed that the resistance of Helicoverpa armigera to Cry1Ac was autosomal, partially recessive and polygenic. Similar conclusions were obtained for populations of Plutella xylostella (Sayyed et al, 2000), Heliothis virescens , and Pectinophora gossypiella (Kaur and Dilawari, 2011).…”
Section: Sustainability Of Biocontrol Agent Efficacymentioning
confidence: 99%
“…The results suggest that the increased resistance (72-fold compared to susceptible strain) 11 to Cry1Ac in laboratory-selected resistant strain (BM-R) differs when exposed to Bt-cotton leaves. Tests on cotton leaves using progeny of BM-R strain continuously selected for 19 generations on diet-incorporated Cry1Ac (MVP-II) showed only 0.15% survival.…”
mentioning
confidence: 91%
“…These studies indicate the potential of these insects to develop resistance to Bt-toxins. Laboratory experiments for resistance study in India have shown tolerance in H. armigera under laboratory conditions [10][11][12][13] . In Mississippi and Arkansas, USA, Bt-resistance in bollworm, Helicoverpa zea on Bt-cotton has been reported 14 .…”
mentioning
confidence: 99%
See 2 more Smart Citations